2018
DOI: 10.1007/s00429-018-1784-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contributions to sequence prediction in verbal working memory

Abstract: Verbal working memory is one of the most studied non-motor functions with robust cerebellar involvement. While the superior cerebellum (lobule VI) has been associated with articulatory control, the inferior cerebellum (lobule VIIIa) has been linked to phonological storage. The present study was aimed to elucidate the differential roles of these regions by investigating whether the cerebellum might contribute to verbal working memory via predictions based on sequence learning/detection. 19 healthy adult subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 81 publications
(121 reference statements)
3
15
0
Order By: Relevance
“…These results are in broad agreement with others, and suggest extensive areas of the cerebellum are involved in working memory (Chen & Desmond, 2005a;Chen & Desmond, 2005b;Desmond et al, 1997;Guell et al, 2018;Keren-Happuch et al, 2014;Stoodley et al, 2012;Tomlinson, Davis, Morgan, & Bracewell, 2014). A recent study (Peterburs, Blevins, Sheu, & Desmond, 2019), which also used a Sternberg paradigm, found that BOLD activity in Lobule VIII (previously shown to be involved in maintenance, Kirschen et al, 2010), increased with working memory load. Taken together, these findings provide evidence of a role for the cerebellum in sequence rehearsal, detection, and prediction in relation to VWM.…”
Section: Cognitive Functionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in broad agreement with others, and suggest extensive areas of the cerebellum are involved in working memory (Chen & Desmond, 2005a;Chen & Desmond, 2005b;Desmond et al, 1997;Guell et al, 2018;Keren-Happuch et al, 2014;Stoodley et al, 2012;Tomlinson, Davis, Morgan, & Bracewell, 2014). A recent study (Peterburs, Blevins, Sheu, & Desmond, 2019), which also used a Sternberg paradigm, found that BOLD activity in Lobule VIII (previously shown to be involved in maintenance, Kirschen et al, 2010), increased with working memory load. Taken together, these findings provide evidence of a role for the cerebellum in sequence rehearsal, detection, and prediction in relation to VWM.…”
Section: Cognitive Functionsupporting
confidence: 90%
“…However, a recent imaging study has shown that performance of the Sternberg task does not result in contamination of cerebellar activity related to eye movements (Peterburs et al, 2016). A recent study (Peterburs, Blevins, Sheu, & Desmond, 2019), which also used a Sternberg paradigm, found that BOLD activity in Lobule VIII (previously shown to be involved in maintenance, Kirschen et al, 2010), increased with working memory load. Load was associated with widespread activity in bilateral Crus I, right Crus II, and right Lobules VI and VIII, with greatest activity in the right cerebellar hemisphere.…”
Section: Cognitive Functionmentioning
confidence: 97%
“…Moreover, in a recent neuroimaging study, participants were asked to complete a Sternberg task that included repeating and novel letter sequences. The results indicated that activations in cerebellar regions contribute to verbal working memory by generating predictions of letter sequences, which supports the hypothesis of sequence learning, detection, and prediction (Peterburs, Blevins, Sheu, & Desmond, 2019 ).…”
Section: Introductionsupporting
confidence: 83%
“…This confirms the functional role of the cerebellum in social sequence detection and learning. Note that it is quite unlikely that the stronger activation of social sequence learning is simply due to higher memory load and executive effort required for social sentences in comparison with nonsocial sentences, because retrieval accuracy was almost identical across these two conditions, and activation was opposite to that reported for higher verbal memory load in recent research (deactivation: Peterburs et al, 2019). Other potential differences between these conditions, such as a greater motivational and emotional impact of social sentences might contribute to the stronger activation of the posterior cerebellum, although these are inherent (and often desired) aspects of social action, which cannot easily be eliminated.…”
Section: Posterior Cerebellum and Learning Social Action Sequencesmentioning
confidence: 80%
“…Based on earlier finds, SCL is involved in articulatory control and non-motor cognitive function (Ferenci et al, 2002). The left FG plays a critical role in semantic dementia and is repeatedly reported to be involved in visual word processing (Peterburs et al, 2019). SFG, which is located on top of the brain, plays a role in several higher-level cognitive processes and working memory according to a previous report (Alagapan et al, 2019).…”
Section: Discussionmentioning
confidence: 90%